2023
DOI: 10.3389/fragi.2023.1202152
|View full text |Cite
|
Sign up to set email alerts
|

The central role of DNA damage in immunosenescence

Abstract: Ageing is the biggest risk factor for the development of multiple chronic diseases as well as increased infection susceptibility and severity of diseases such as influenza and COVID-19. This increased disease risk is linked to changes in immune function during ageing termed immunosenescence. Age-related loss of immune function, particularly in adaptive responses against pathogens and immunosurveillance against cancer, is accompanied by a paradoxical gain of function of some aspects of immunity such as elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 189 publications
0
4
0
Order By: Relevance
“…Telomere attrition is a phenomenon that arises from cellular replication and is expedited by diverse environmental conditions, including inflammation and oxidative stress [126][127][128]. Oxidative stress has been recognized as a physiological factor contributing to telomere shortening, which in turn is associated with human aging by several mechanisms [127][128][129][130][131][132][133][134]. Overall, it has been suggested that the repair of oxidative damage in telomeric DNA is comparatively less efficient than in other chromosome regions [126,135].…”
Section: Discussionmentioning
confidence: 99%
“…Telomere attrition is a phenomenon that arises from cellular replication and is expedited by diverse environmental conditions, including inflammation and oxidative stress [126][127][128]. Oxidative stress has been recognized as a physiological factor contributing to telomere shortening, which in turn is associated with human aging by several mechanisms [127][128][129][130][131][132][133][134]. Overall, it has been suggested that the repair of oxidative damage in telomeric DNA is comparatively less efficient than in other chromosome regions [126,135].…”
Section: Discussionmentioning
confidence: 99%
“…In the lung, PM 10 exposure has been linked to senescence [9]. One of the causes of senescence is DNA damage [10]. PM 10 induces DNA damage by oxidative stress, which causes double-strand breaks (DSBs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…PM 10 induces DNA damage by oxidative stress, which causes double-strand breaks (DSBs) [10]. DNA damage mobilizes phosphoinositide 3kinase-related protein kinases (PIKKs), as well as ataxia telangiectasia-mutated (ATM), and Rad-3-related kinase (ATR) [10]. These kinases activate tumor suppressor p53 further downstream [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation